2008
DOI: 10.1103/physrevb.77.104519
|View full text |Cite
|
Sign up to set email alerts
|

CuK-edge resonant inelastic x-ray scattering in edge-sharing cuprates

Abstract: We present calculations for resonant inelastic x-ray scattering (RIXS) in edge-shared copper oxide systems, such as Li2CuO2 and CuGeO3, appropriate for hard x-ray scattering such as the copper K-edge. We perform exact diagonalizations of the multi-band Hubbard model and determine the energies, orbital character and resonance profiles of excitations which can be probed via RIXS. We find excellent agreement with recent results on Li2CuO2 and CuGeO3 in the 2-7 eV photon energy loss range.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 43 publications
(38 reference statements)
2
48
0
Order By: Relevance
“…The relatively large separation in energy from the valence levels as well as the large spatial extent of the 4p orbital are believed to prevent the photoelectron from interacting with the valence system, and this type of RIXS is in turn referred to as indirect. 6 Accordingly, theoretical models of this type of RIXS accordingly do not include possible interactions of the 4p photoelectron with the valence system, 12-15 which is commonly referred to as the '4p-as-spectator' approximation.RIXS investigations of the photon polarization effects have so far concluded that the incident polarization does not affect the probed valence band excitations, but only determines their specific resonance energies based on the crystal field levels of the 4p photoelectron, 14,16,17 in accordance with the 4p-as-spectator approximation. Nonetheless, there still exists no quantitative experimental evidence for an incident-photon polarization independence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively large separation in energy from the valence levels as well as the large spatial extent of the 4p orbital are believed to prevent the photoelectron from interacting with the valence system, and this type of RIXS is in turn referred to as indirect. 6 Accordingly, theoretical models of this type of RIXS accordingly do not include possible interactions of the 4p photoelectron with the valence system, 12-15 which is commonly referred to as the '4p-as-spectator' approximation.RIXS investigations of the photon polarization effects have so far concluded that the incident polarization does not affect the probed valence band excitations, but only determines their specific resonance energies based on the crystal field levels of the 4p photoelectron, 14,16,17 in accordance with the 4p-as-spectator approximation. Nonetheless, there still exists no quantitative experimental evidence for an incident-photon polarization independence.…”
mentioning
confidence: 99%
“…The relatively large separation in energy from the valence levels as well as the large spatial extent of the 4p orbital are believed to prevent the photoelectron from interacting with the valence system, and this type of RIXS is in turn referred to as indirect. 6 Accordingly, theoretical models of this type of RIXS accordingly do not include possible interactions of the 4p photoelectron with the valence system, [12][13][14][15] which is commonly referred to as the '4p-as-spectator' approximation.…”
mentioning
confidence: 99%
“…Spectral intensities were calculated using the KramersHeisenberg formula [11] with the optical transition operator expressed in the hole representation: O k ¼ P j; p y j; d j; e ikÁr j , d removing a hole in the 3d band and p y creating one in the Cu 2p shell. The presence of a Cu 2p core-hole in the intermediate states was accounted for by an on-site Coulomb interaction [33]. The calculated RIXS profiles for the accessible k points are displayed in Fig.…”
mentioning
confidence: 99%
“…The most exciting puzzle addressed here is the missing of the ZhangRice singlet peak (ZRS) in reflectivity and electron energy loss spectroscopy (EELS) data at T = 300 K 1,2 . Its detection in resonant inelastic x-ray scattering (RIXS) spectra is under debate, too 4,5 . There is also no consensus on the role of two scenarios for the FM in-chain order below the Néel temperature T N = 9 K. Scenario I is given by a dominant FM J 1 9 defined by the inequality α = −J 2 /J 1 < α c ≈ 0.25, if J 3 is weak 13 , where α c marks the transition from a high-spin FM to a lowspin spiral-like ground state (GS).…”
mentioning
confidence: 99%
“…This will cause a strong T -dependence of various response functions, here presented for the case of the optical conductivity σ(ω). For an illustration of our approach we consider Li 2 CuO 2 being of current interest 1,2,3,4,5,6,7,8,9,10,11,12 , structurally simple, and most importantly, where single crystal data are available in a broad ω-range 1,2 . This system stands for a class of frustrated spin-1/2 chain materials with both small ferromagnetic (FM) NN Cu-Cu exchange coupling J 1 and AFM next-nearest neighbor (NNN) Cu-Cu in-chain exchange J 2 1,3 in terms of a 1D spin-1/2 Heisenberg model…”
mentioning
confidence: 99%